Characteristics and Empirical Modelling of Extract from Hibiscus sabdariffa Using Supercritical CO2 Extraction with Ethanol-Water as Modifier - Idham, Z. (Springer Science and Business Media Deutschland GmbH, 2021)
The main constituents of the extract from Hibiscus sabdariffa calyces are anthocyanins which gave intense natural red colorant and commonly used for centuries for therapeutic purposes. Supercritical carbon dioxide (SC-CO2) technique could produce high-quality extracts from plant materials as it can exploit the non-toxic character and the gasâliquid properties of the SC-CO2. This research aimed to characterise the colour and the pattern of Hibiscus sabdariffa SC-CO2 extraction. The colour was evaluated by using a CIELAB method meanwhile the presence of anthocyanins in the red colour extract was confirmed by High-Performance Liquid Chromatograph (HPLC). Two types of empirical models (Modified Brunnerâs and Esquivelâs models) were used to describe the extracts obtained at series of operational parameters (i.e. pressure and temperature) at 7.5 and 10 of modifier ratio, with a total solvent flow rate of 4Â ml/min. Both models were analysed using a non-linear regression method. The modified Brunnerâs model shows the best agreement between experimental and model calculated data with the lowest AARD of 1.30 at 70Â Â°C, 10Â MPa, and 10 modifier ratio. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.